The Influence of Motivation and Work Discipline on Employee Performance at PT Artindo Pratama Sejahtera, Serang Branch - Amelia Rahmadani; Teguh Kurniyanto (Takaza Innovatix Labs Ltd., 2026)
Employee performance is a crucial factor in determining an organization's success in achieving its goals. The decline in work motivation and work discipline at PT Artindo Pratama Sejahtera Serang Branch indicates problems that may reduce productivity and work effectiveness. This study aims to analyze the effect of work motivation and work discipline on employee performance, both partially and simultaneously. This research employed a quantitative approach with a descriptive-associative design. The population consisted of 142 employees, while 59 respondents were selected as the sample using the Slovin formula with a non-probability sampling technique. Data were collected through observation, questionnaires, and literature review, and were analyzed using multiple linear regression with IBM SPSS software. The results revealed that work motivation had a positive and significant effect on employee performance (t = 2.784; p = 0.007). Likewise, work discipline also had a positive and significant effect on employee performance (t = 2.765; p = 0.008). Simultaneously, work motivation and work discipline significantly influenced employee performance (F = 13.139; p = 0.000), with a coefficient of determination of 31.9%. It can be concluded that improving work motivation and work discipline plays an important role in enhancing employee performance. Therefore, companies should strengthen human resource management policies to improve productivity and support the achievement of organizational objectives.